Novel Aspects of Renal Magnesium Homeostasis - Giménez-Mascarell, Paula; Schirrmacher, Carlotta Else; Martínez-Cruz, Luis Alfonso; Müller, Dominik (Frontiers in Pediatrics, 2018)
Magnesium (Mg2+) is indispensable for several vital functions such as neurotransmission, cardiac conductance, blood glucose, blood pressure regulation and proper function of more than 300 enzymes. Thus, Mg2+ homeostasis is subject to tight regulation. Besides the fast and immediate regulation of plasma Mg2+, a major part of Mg2+ homeostasis is realized by a concerted action of epithelial molecular structures that tightly control intestinal uptake and renal absorption. This mechanism is provided by a combination of para- and transcellular pathways. Whereas the first pathway provides the organism with a maximal amount of vital substances by a minimal energy expenditure, the latter enables controlling and fine-tuning by means of local and regional regulatory systems and also, hormonal control. The paracellular pathway is driven by an electrochemical gradient and realized in principal by the tight junction (TJ), a supramolecular organization of membrane-bound proteins and their adaptor and scaffolding proteins. TJ determinants are claudins (CLDN), a family of membrane spanning proteins that generate a barrier or a pore between two adjacent epithelial cells. Many insights into molecular mechanisms of Mg2+ handling have been achieved by the identification of alterations and mutations in human genes which cause disorders of paracellular Mg2+ pathways (CLDN10, CLDN14, CLDN16, CLDN19). Also, in the distal convoluted tubule, a basolateral protein, CNNM2, causes if mutated, familial dominant and also recessive renal Mg2+ wasting, albeit its true function has not been clarified yet, but is assumed to play a key role in the transcellular pathway. Moreover, mutations in human genes that are involved in regulating these proteins directly or indirectly cause, if mutated human diseases, mostly in combination with comorbidities as diabetes, cystic renal disease or metabolic abnormalities. Generation and characterization of animal models harboring the corresponding mutations have further contributed to the elucidation of physiology and pathophysiology of Mg2+ disorders. Finally, high-end crystallization techniques allow understanding of Mg2+ handling in more detail. As this field is rapidly growing, we describe here the principles of physiology and pathophysiology of epithelial transport of renal Mg2+ homeostasis with emphasis on recently identified mechanisms involved.